Need Analysis of English Learning in the Digital Era for Vocational Higher Education Students - Widi Sriyanto; Nurianti Sitorus (Universitas Cokroaminoto Palopo, 2021)
This study aims to describe the needs analysis of basic English (General English) courses for vocational higher education students, focusing on analyzing targets and learning needs. Data were obtained from questionnaires and interviews. The research results in the form of target analysis indicate that the purpose of learning English for vocational students is to communicate using English actively both orally and in writing. The results of the analysis of learning needs obtained are that students need the ability to speak fluently and communicatively and write correctly and adequately to prepare themselves to meet the demands of their profession. This shows that the desire of students to improve their speaking and writing skills is very much in line with the needs of the industry, which requires the ability to communicate in English both orally and in writing well. The results of this study are expected to be a reference for preparing the syllabus and developing textbooks.